USE OF THE SYSTEM RESERVATIONS IN THE FRONT OFFICE DEPARTMENT OF THE GRAND SUKA HOTEL PEKANBARU - Farhan, Ibnu; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to find out about the procedures for ordering forms for the Front Office Department at the Grand Suka Hotel Pekanbaru. The reservation form is the process of creating a list of incoming guest orders in accordance with existing procedures. Suka is an abbreviation for "Sultan Kasim" which was inaugurated in 2016, Grand Suka Hotel Pekanbaru is centrally located on Jalan Soekarno-Hatta, Pekanbaru, which is a subsidiary of PT. SUKA SURYA INTERNUSA. This research uses qualitative methods to analyze a collection of cases consisting of three key informants in this research. That is 1 Duty Manager, 1 Reservations Staff, and 1 Front Desk Agent. Sources were obtained through interviews, observation and documentation. Based on the results of the research, the conclusion of this research is that the front office department reservation form has been implemented, but improvements still need to be made so that the reservation form will be better in the future. Keywords: Reservation form, Front Office, Hotel